Implementing local economic development in Ghana: Multiple actors and rationalities - Jonas Ayaribilla Akudugu; Wolfram Laube (University of Bonn, Center for Development Research (ZEF), 2013)
International development agencies continue to influence the development agenda of many developing countries. One of the latest development strategies being promoted by these bodies is local economic development (LED). The introduction of contemporary LED practice, where local stakeholders and authorities, in partnership with national planning agencies and international donors, jointly identify, design, and implement initiatives aimed at stimulating the local economy, is supposed to mark a paradigm shift from top-down approaches to bottom-up approaches of local development. Through this approach, development actors operating at the sub-national level are expected to mobilize local resources to implement LED initiatives, thus reducing reliance on central government and donor funds. This LED approach, in the estimation of international development agencies, eventually promotes subsidiarity and self-reliance at the district level. However, in Ghana, soon after the introduction of this presumably promising development strategy, it became clear that LED approaches are only partially adopted in local development planning and are hardly implemented, as they do not match the strategies and rationalities of key actors planning and implementing local development initiatives. While nationaland district-level planning agencies remain devoted to top-down development planning, local stakeholders are instead interested in infrastructure development and the direct transfer of funds, rather than participatory planning exercises meant to enhance local economic dynamics and competitiveness. This paper shows how LED as an externally introduced development strategy that does not fit well into the technical, social, economic, and political rationalities of local actors and as such is bound to fail, irrespective of its theoretical potential and the external support provided for its implementation. This paper explores the structural environment as well as multiple rationalities and interests that seem to impede the implementation of LED in Ghana.
Keywords: 330; Development intervention; local economic development; actors; rationalities; policy implementation